2013
DOI: 10.1186/1471-2466-13-58
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and corticosteroid responsiveness in ex-, current- and never-smoking asthmatics

Abstract: BackgroundIt has been suggested that smoking asthmatics benefit less from corticosteroid treatment than never-smoking asthmatics. We investigated differences in blood and sputum inflammatory profiles between ex-, current-, and never-smokers and assessed their ICS treatment response after 2-week and 1-year treatment.MethodsWe analyzed FEV1, PC20 methacholine and PC20 AMP, (differential) cell counts in sputum and blood in ex-, current- and never-smokers at baseline (n=114), after 2-week treatment with fluticason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 33 publications
5
47
1
Order By: Relevance
“…2628 Similarly, lower BMI and non-smoking status as predictors are not unexpected, because the obesity-related asthma phenotype is typically noneosinophilic, 1,2 and current and ex-smokers have lower blood eosinophils than never-smokers. 2729 The proportion of patients with peripheral eosinophilia (16%) in the present study was similar to the 18-26% prevalence found among adults with asthma in three recent observational studies using a similar cut-point (<400/µL vs. ≥400/µL). 15,17, 19 Zeiger et al 17 in a study of 2392 adults with asthma found that blood eosinophil count ≥400/µL was a risk factor for asthma exacerbation the following year as well as for excessive SABA use (≥4 puffs/day, equivalent to ≥400 µg/day in this study).…”
Section: Discussionsupporting
confidence: 71%
“…2628 Similarly, lower BMI and non-smoking status as predictors are not unexpected, because the obesity-related asthma phenotype is typically noneosinophilic, 1,2 and current and ex-smokers have lower blood eosinophils than never-smokers. 2729 The proportion of patients with peripheral eosinophilia (16%) in the present study was similar to the 18-26% prevalence found among adults with asthma in three recent observational studies using a similar cut-point (<400/µL vs. ≥400/µL). 15,17, 19 Zeiger et al 17 in a study of 2392 adults with asthma found that blood eosinophil count ≥400/µL was a risk factor for asthma exacerbation the following year as well as for excessive SABA use (≥4 puffs/day, equivalent to ≥400 µg/day in this study).…”
Section: Discussionsupporting
confidence: 71%
“…We also saw an increase in absolute numbers of neutrophils in the blood and a decrease in FeNO in the SAs/ex group compared with the SAn group. These effects are also reported in milder asthma [30][31][32]. Other inflammatory changes observed in response to smoking in milder asthma include a reduction in blood [30] and sputum eosinophils [30,33], increases in sputum neutrophils [29], and increased submucosal CD8 + lymphocytes and macrophages in bronchial biopsies [34]; however, we did not see these differences in our severe asthma subjects.…”
Section: Discussioncontrasting
confidence: 50%
“…From a pragmatic, clinical perspective, phenotypic traits can be used in the daily clinical care to target-specific treatments: eosinophilia combined with exacerbations predicts effect of anti-IL5 [27] and patients with fixed airflow obstruction and exacerbations may benefit from tiotropium [28]. Furthermore, perennial allergic sensitization, airflow obstruction (FEV1 < 80%) and exacerbations predict effect of anti-IgE [5].…”
Section: Systematic Assessment Of Severe Asthmamentioning
confidence: 99%